2019
DOI: 10.1093/nar/gkz139
|View full text |Cite
|
Sign up to set email alerts
|

Biclustering analysis of transcriptome big data identifies condition-specific microRNA targets

Abstract: We present a novel approach to identify human microRNA (miRNA) regulatory modules (mRNA targets and relevant cell conditions) by biclustering a large collection of mRNA fold-change data for sequence-specific targets. Bicluster targets were assessed using validated messenger RNA (mRNA) targets and exhibited on an average 17.0% (median 19.4%) improved gain in certainty (sensitivity + specificity). The net gain was further increased up to 32.0% (median 33.4%) by incorporating functional networks of targets. We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…It is known that weak repression by miRNAs can nevertheless have a substantial effect on cell phenotype ( Flynt & Lai, 2008 ). Recently, data have been obtained supporting an FC threshold as low as 1.3 for functional miRNA targets ( Yoon et al, 2019 ). This threshold can apply to the miRNA-induced mRNA up-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that weak repression by miRNAs can nevertheless have a substantial effect on cell phenotype ( Flynt & Lai, 2008 ). Recently, data have been obtained supporting an FC threshold as low as 1.3 for functional miRNA targets ( Yoon et al, 2019 ). This threshold can apply to the miRNA-induced mRNA up-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Different from other biological networks (i.e., protein-protein interaction network), the miRNA–target regulatory network is a bipartite network. Consequently, the generated miRNA–target modules are actually bicliques where every miRNA of the miRNA set is connected to each target gene of the target gene set ( Yoon et al, 2019 ). In this work, we utilize the R package biclique ( Zhang et al, 2014 ) to enumerate all bicliques from the identified miRNA–target bipartite network.…”
Section: Methodsmentioning
confidence: 99%
“…Biclustering has been successfully applied to hundreds of problems in the biological and biomedical domain and has supported detection of functional annotations (e.g., gene regulatory pathways), as well as biological interactions (e.g., transcriptional networks), the discovery of drugs and biomarkers, identification of subtypes of diseases, and analysis of responses to treatments [6]. A biclustering method has also helped to identify novel human microRNA regulatory modules [2]. Biclustering techniques have been also been successfully used in graph analysis, text mining, recommendation systems, marketing, economy (e.g., market segmentation), analysis of sports data, and multiple other domains [1].…”
Section: What Is Biclustering?mentioning
confidence: 99%